The different activities of RNA G-quadruplex structures are controlled by flanking sequences - Zheng, Alice J-L; Thermou, Aikaterini; Guixens Gallardo, Pedro; Malbert-Colas, Laurence; Daskalogianni, Chrysoula; Vaudiau, Nathan; Brohagen, Petter; Granzhan, Anton; Blondel, Marc; Teulade-Fichou, Marie-Paule; Martins, Rodrigo Prado; Fahraeus, Robin (Life science alliance, 2022)
The role of G-quadruplex (G4) RNA structures is multifaceted and controversial. Here, we have used as a model the EBV-encoded EBNA1 and the Kaposi's sarcoma-associated herpesvirus (KSHV)-encoded LANA1 mRNAs. We have compared the G4s in these two messages in terms of nucleolin binding, nuclear mRNA retention, and mRNA translation inhibition and their effects on immune evasion. The G4s in the EBNA1 message are clustered in one repeat sequence and the G4 ligand PhenDH2 prevents all G4-associated activities. The RNA G4s in the LANA1 message take part in similar multiple mRNA functions but are spread throughout the message. The different G4 activities depend on flanking coding and non-coding sequences and, interestingly, can be separated individually. Together, the results illustrate the multifunctional, dynamic and context-dependent nature of G4 RNAs and highlight the possibility to develop ligands targeting specific RNA G4 functions. The data also suggest a common multifunctional repertoire of viral G4 RNA activities for immune evasion.
Keywords: Gene Expression Regulation; RNA, Viral; DNA, Intergenic; transport RNA; virus Epsteinův-Barrové - jaderné antigeny; RNA virová; G-kvadruplexy; lidé; Epstein-Barr Virus Nuclear Antigens; RNA; RNA Transport; Humans; G-Quadruplexes; regulace genové exprese; intergenová DNA